Application of Balanced Scorecard in Performance Management and Evaluation of Listed Companies - Xuqin Song (Discrete Dynamics in Nature and Society)
A reasonable enterprise performance evaluation system not only is conducive to the scientific nature of enterprise internal management, but also can accurately reflect the shortcomings in development and provide effective guidance for the high-quality and efficient development of enterprises. Therefore, based on the relevant theories and research of performance evaluation and balanced scorecard (BSC), this paper analyzes the shortcomings of the current performance evaluation system of enterprises and the necessity and feasibility of applying BSC to design performance evaluation system. Then, we design a performance evaluation system with the characteristics of listed companies (LC). Finally, we use the analytic hierarchy process (AHP) to conduct a comprehensive performance evaluation of enterprise A and propose corresponding safeguards for the smooth implementation of the system according to the evaluation results.